Activity‐dependent global model of electron loss inside the plasmasphere. Issue 11 (12th June 2014) - Orlova, Ksenia; Spasojevic, Maria; Shprits, Yuri
Abstract Using data from the CRRES plasma wave experiment, we develop quadratic fits to the mean of the wave amplitude squared for plasmaspheric hiss as a function of Kp, L, and magnetic latitude (λ) for the dayside (6 < magnetic local time (MLT) ≤ 21) and nightside (21 < MLT ≤ 6) magnetic local time sectors. The empirical model of hiss waves is used to compute quasi‐linear pitch angle diffusion coefficients for energetic, relativistic, and ultrarelativistic electrons in the energy range of 1 keV to 10 MeV. In our calculations, we account for changes in hiss wave normal angle and plasma density with increasing λ. Electron lifetimes are then calculated from the diffusion coefficients and parameterized as a function of energy, Kp, and L. Coefficients for both the hiss model and the electron lifetimes are provided and can be easily incorporated into existing diffusion, convection, and particle tracing codes.